(untitled) (Bangladesh Journal of Child Health, 2017)
Background: Celiac disease is (CD) a genetically determined chronic inflammatory disease induced by an environmental precipitant. It is a multisystem disease and can develop at any point of time during life in genetically susceptible individuals upon ingestion of wheat gluten and related cereal proteins. The onset of symptoms in the atypical form generally occurs between 4-15 years of age. Diagnosis of CD with extraintestinal manifestations is frequently missed as it presents without diarrhoea. Objective: To observe the frequency of celiac disease in children with liver disease. Methods: This cross sectional study was conducted at BSMMU from January 2014 to June 2015. A total of 59 children (age 18 months to16 years) with clinical and biochemical features of liver disease were initially enrolled for the study. Their clinical history, examination findings and investigation reports were recorded in a data collection sheet and informed consent was obtained from parents. Routine investigations, liver function tests, tissue transglutaminase tTG (IgA), total IgA. were done. After exclusion of other causes of liver disease endoscopy of upper gastrointestinal tract (GIT) was done on patients who were tTG (titer of >50 iu/mL) positive. Patients who were tTG negative but found IgA deficient (1 patient) was also selected for upper GI endoscopy and biopsy fragments were taken from second part of duodenum (D2) sent for histopathology. Results: Mean age of studied children was 8.33 ± 3.64 years. Out of 59 children with liver disease, 32.2% were tTG positive of whom female were 8 (13.6%) and male 11 (18.6%). Mean age at diagnosis of all patients with tTG positive group was 8.24 ± 2.78 (range 4-12) years. Among 19 sero-positive patients, short stature was found in 57.9% children. Mean Hb level in tTG positive group was 8.83 ± 2.64 gm/dl and in tTG negative group (10.27 ± 1.74 gm/dl). Sixteen (84.2%) out of 19 tTG positive patients had raised S. ALT. Out of 19 tTG positive children, endoscopy was done in 15 cases (endoscopy could not be done in 4 patients due to persistently raised PT) along with 1 patient who was IgA deficient. Endoscopic changes were mosaic and scalloping of D2 mucosa in 1 and 2 cases respectively. Histological changes compatible with CD were found in 5 (31.3%) patients. Marsh 3a category was found in 2 (12.5%) cases and 3b in 3 (18.8%) cases. Conclusion: In the present study, 32.2% liver disease cases were found tTG positive. Histological changes compatible with CD were found in about one-third cases. Screening for celiac disease may be included in the diagnostic tests for evaluation of liver disease in children. Bangladesh J Child Health 2016; VOL 40 (3) :144-148